The inhibitors - a challenge for the management of patients with hereditary haemophilia A - Mihăilă Romeo-Gabriel (Sciendo, 2018)
Introduction. Our research strategy was aimed at evaluating the possible implication of the type of factor VIII product administered as substitution treatment to haemophilia A patients in the occurrence of inhibitors and their consequences on the management.